Science Literacy Support for Improving Students Argumentation Skills - Irawan, Laura Alden Litha Miranda; Suyono, Suyono (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
This study explores the impact of science literacy on improving students' argumentation skills at SMA Negeri 21 Surabaya during the 2023/2024 academic year, within the context of the